Gottfried Ostermeyer and his Descendants in Lithuanian Writing - Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2016)
The paper presents new bibliographical information on Gottfried Ostermeyer (1716–1800), a pastor of Trempai and a famous eighteenth-century figure of writing of Lithuania Minor, and on his descendants. It mentions their works in the field of Lithuanian studies and the latest studies into them. It also makes references to printed works and manuscripts that have not been found or have not survived. Representatives of four Ostermeyer generations worked for the Lithuanian cause, and the paper offers the genealogical chart of the Ostermeyer branch associated with activities in Lithuanian studies. Gottfried Ostermeyer was a historiographer of Lithuanian literature, an author of a Lithuanian grammar, a compiler of a Lithuanian hymnal, and a historical and mythological scholar. It is his works in Lithuanian studies that the general public knows best. His son Siegfried Ostermeyer (1759–1821) became known for his polemic treatise Ist es anzurathen die litthauische Sprache zu verdrängen und die Litthauer mit den Deutschen zu verschmelzen? (Is it Advisable to Force out the Lithuanian Language and to Merge Lithuanians with Germans?, Gumbinnen, 1818). Published as a separate book, it was provoked by an anonymous letter that had appeared in a literary newspaper of Jena, Jenaische Literatur-Zeitung, in 1814 and called for forcing out local languages (Lithuanian and Polish) of East Prussia as lacking any prospects and hindering aspirations towards higher culture. Justine Ostermeyer, Gottfried Ostermeyer’s daughter, was the first woman known to collect Lithuanian folklore. Five grandsons of Gottfried Ostermeyer (the sons of Siegfried Ostermeyer) – Nataniel Friedrich, Gottfried Lebrecht, Bernhard Wilhelm, Karl Heinrich, and Siegfried Gustaw, and the great-grandson of Gottfried Ostermeyer (the son of Nataniel Friedrich) Albert Julius Ostermeyer nurtured the Lithuanian spirit in Lithuania Minor in a variety of ways. They taught Lithuanian at Königsberg University, published periodicals, translated sermons and religious educational readers into Lithuanian, collected folklore, worked as teachers and pastors in Lithuanian churches. From the point of view of Lithuanian studies, the paper complements the genealogical study of the Ostermeyer family, Die Ostermeyer alias Ostermayr. Genealogische Studie (Ostermeyer, also known as Ostermayr. A Genealogical Study; 1903), prepared by the great-great-grandson of Gottfried Ostermeyer, Paul Rudolf Ostermeyer (1859–?), who was a preacher at the Sakaimis (Sackheim) church in Königsberg. The present study addresses literary activities of Gottfried Ostermeyer and his son Siegfried insufficiently, while the relation of Gottfried Ostermeyer’s five grandsons and his great-grandson with Lithuanian studies and the Lithuanian spirit is not mentioned at all.